Study of the technologies for biodiesel production from microalgae of the genus nannochloropsis (Research, Society and Development, 2018)
The biodiesel difficulties to be implemented due to its high cost associated with the many stages of the production process. In this way, studies are necessary to make the process economically viable. The present article aims to identify the main results of high relevance scientific papers that point out techniques of biodiesel production from microalgae of the genus nannochloropsis. To do so, a systematic review of the Web of Science database with the help of CiteSpace and Google Earth software was carried out, in which it was observed that a promising method consists of direct transesterification of the microalgae, which eliminates the oil extraction step. Another highlight is the use of humid biomass. These methods simplify the biodiesel production process and reduce the processing units and consequently the overall process cost, helping to make biodiesel production of microalgae economically viable.